Mechanisms of postprandial abdominal bloating and distension in functional dyspepsia. Issue 3 (4th May 2013) - Burri, Emanuel; Barba, Elizabeth; Huaman, Jose Walter; Cisternas, Daniel; Accarino, Anna; Soldevilla, Alfredo; Malagelada, Juan-R; Azpiroz, Fernando
Abstract : Objective: Patients with irritable bowel syndrome and abdominal bloating exhibit abnormal responses of the abdominal wall to colonic gas loads. We hypothesised that in patients with postprandial bloating, ingestion of a meal triggers comparable abdominal wall dyssynergia. Our aim was to characterise abdominal accommodation to a meal in patients with postprandial bloating. Design: A test meal (0.8 kcal/ml nutrients plus 27 g/litre polyethylenglycol 4000) was administered at 50 ml/min as long as tolerated in 10 patients with postprandial bloating (fulfilling Rome III criteria for postprandial distress syndrome) and 12 healthy subjects, while electromyographic (EMG) responses of the anterior wall (upper and lower rectus, external and internal oblique via bipolar surface electrodes) and the diaphragm (via six ring electrodes over an oesophageal tube in the hiatus) were measured. Means +/− SD were calculated. Results: Healthy subjects tolerated a meal volume of 913±308 ml; normal abdominal wall accommodation to the meal consisted of diaphragmatic relaxation (EMG activity decreased by 15±6%) and a compensatory contraction (25±9% increase) of the upper abdominal wall muscles (upper rectus and external oblique), with no changes in the lower anterior muscles (lower rectus and internal oblique). Patients tolerated lower volume loads (604±310 ml; p=0.030 vs healthy subjects) and developed a paradoxical response, that is, diaphragmatic contraction (14±3% EMG increment; p<0.01 vs healthy subjects) and upper anterior wall relaxation (9±4% inhibition; p<0.01 vs healthy subjects). Conclusions: In functional dyspepsia, postprandial abdominal distension is produced by an abnormal viscerosomatic response to meal ingestion that alters normal abdominal accommodation.